2005
DOI: 10.2174/1573402052952843
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Antihypertensive Treatment on the Bone Mineral Density and Osteoporotic Fracture

Abstract: The financial and social cost of hypertension and osteoporosis, clinically silent diseases, are determined by the consequences, such as a vascular disease and fractures. The relationship between these illnesses has not been clearly established, although many alterations in extracellular metabolism of calcium, which could determine the level of bone mineral density (BMD) in these patients, have been associated to hypertension. Despite these alterations, the lack of studies relating these two important diseases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…Prior studies have demonstrated that bone loss is positively associated with both systolic and diastolic blood pressure (Metz et al, 1999; Rejnmark et al, 2006). Persons with hypertension have increased urinary calcium excretion and increased mobilization of calcium from the bones (Cappuccio et al, 1999; Metz et al, 1999; Perez-Castrillon et al, 2005). These changes are thought to occur either as a result of increased blood volume (as sodium intake is also positively associated with calcium excretion (Cappuccio et al, 1999)) or as a result of a disorder within the kidney tubule (Ilic et al, 2013).…”
Section: Collateral Health Risks Among Older Adults With Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have demonstrated that bone loss is positively associated with both systolic and diastolic blood pressure (Metz et al, 1999; Rejnmark et al, 2006). Persons with hypertension have increased urinary calcium excretion and increased mobilization of calcium from the bones (Cappuccio et al, 1999; Metz et al, 1999; Perez-Castrillon et al, 2005). These changes are thought to occur either as a result of increased blood volume (as sodium intake is also positively associated with calcium excretion (Cappuccio et al, 1999)) or as a result of a disorder within the kidney tubule (Ilic et al, 2013).…”
Section: Collateral Health Risks Among Older Adults With Hypertensionmentioning
confidence: 99%
“…Diminished intake of vitamins D and K, which are each important to calcium absorption (Ilic et al, 2013), may also play a role. In either case, decreased serum calcium stimulates parathyroid hormone which further increases bone turnover (Perez-Castrillon et al, 2005). Meanwhile, angiotensin II activity has also been reported to contribute to osteoporosis by activating osteoclasts while impairing osteoblast activity (Asaba et al, 2009; Li et al, 2014; Shimizu et al, 2008).…”
Section: Collateral Health Risks Among Older Adults With Hypertensionmentioning
confidence: 99%
“…The prevalence of hypertension among people over the age of 60 years can reach 66%, with more than half of them taking antihypertensive medications . Antihypertensive medications, such as beta‐blockers, thiazide diuretics, angiotensin‐converting‐enzyme (ACE) inhibitors, and the angiotensin II receptor blockers (ARBs), are the most commonly prescribed drugs for people suffering from high blood pressure . Beta‐blockers act by blocking the β‐2 receptor in the sympathetic nervous system resulting in a decrease in blood pressure; thiazide diuretics control hypertension by blocking the thiazide‐sensitive Na‐Cl symporter and inhibiting reabsorption of sodium and chloride ions from the distal convoluted tubules in the kidneys; and ACE inhibitors and ARBs block the renin‐angiotensin system to reduce blood pressure …”
Section: Introductionmentioning
confidence: 99%
“…Arterial hypertension is a chronic disease where the prevalence increases with age, as occurs in osteoporosis [1] . It is clinically silent and is only revealed in the form of complications, an aspect that it also shares with osteoporosis.…”
Section: Introductionmentioning
confidence: 99%